Estudio de prefactibilidad para la instalación de un hotel ecológico en el departamento de Cusco - Abad Zelvaggio, Juan Diego (2020)
The following paper contemplates the general features and the market study for the study of prefeasibility for the implementation of an ecological hotel in the Cusco’s region that has as an objective to analyze the technical, economic and financial viability of the project. In the first chapter, we explain the main aspects in which it has based the investigation, having as a result the hypothesis that it is profitable to locate an ecological hotel in Cusco, compensating it with a service differentiation. In the second chapter, we analyze the industrial sector of lodging in Cusco, and we found a great availability in the market, despite the presence of great hotels franchises that has been operating since many years ago; we have to take advantage of this availability with a high-level service and quality, friendly with the environment. Furthermore, we determine the preliminary prices for this project; starting with S/ 210 in the simple room in the low season with an increment of 50% in the high season. In the analysis realized to determine the location of the hotel, we used the time of travelling, proximity to Machu Picchu, cost of ground and the availability of it; as factors the best place to build it. As a result, the district of Ollantaytambo was chosen. To determine the size of the installations, we used the average of rooms that has every hotel of four stars in the Cusco region, due to; the other relations measured did not apply nor were limiting measures for the project. The result was 88 between, simples, doubles, triples and marital rooms.It was also determined the usage of the technologies for the project, been selected the bio digester, to produce fertilizer; the solar panels, to take advantage of the solar radiation to generate electric energy; and the usage of filters to treat the water coming from the laundry, swimming pool and the showers, to use it as water for irrigation. Last, we determined that the project is viable and profitable, because we obtain a rate of return prudent for the initial investment of S/ 7 950 328; high initial quantity that will be returned during the life cycle of the project. The most important results obtained are that the project is viable both economically and financially, with an economic NPV of S / 4 998 364 and IRR 28.42%, with a financial NPV of S / 5 652 278 and IRR of 38.93%. In addition, the recovery period for this large investment is 4 years, 6 months and 3 days in the economic analysis, and 3 years 5 months and 21 days in the financial analysis.